Representation of Science, Environment, Technology, and Society in Science Comics for Junior High School - Ani Widyawati; Laily Rochmawati Listiyani; Krida Singgih Kuncoro (Universitas Sarjanawiyata Tamansiswa, 2020)
Advances in technology cause a lot of damage to the environment and cultural shifts in society. This condition requires learning to integrate technology with the environment and society. Society-based industrial era 4.0 towards 5.0 studying and technology must pay attention to the preservation of nature and culture in society. The approach that fits this mandate is SETS (science, environment, technology, and society). The SETS approach can be applied in various media, methods and learning models. One of them is a science comic for junior high school that has included the SETS component in its material. This research is a qualitative descriptive study about the relationship between SETS components in junior high school science comics. The instruments in this study were data cards and operational definitions. The data in this study are in the form of words, language, pictures, and behavior that show the representation of the SETS components. The analysis results show that all SETS components have been represented in the science comics. SETS which is integrated into the learning process is expected to improve the quality of students in facing an increasingly advanced industrial era but still environmentally friendly.